Taxation of the Digital Economy: Assessing the Challenges and Opportunities for Governments and Multinational Corporations - Posumah, Lenny M. (Penelitian dan Pengembangan Ilmu, 2024)
This research reveals the challenges and opportunities in digital economy taxation and their application to tax policy and global business practices. The analysis was carried out through in-depth literature observations on key aspects, including tax revenue determination, cross-border transaction management, international collaboration, and digital tax solutions. Findings show that determining taxable income suffers from a variety of challenges, including prevention, tax planning activities, and optimization errors. On the other hand, cross-transaction management requires careful coordination to maintain data consistency and transaction integrity in complex scenarios. International cooperation is important in overcoming the challenges of digital taxation, although there is no international context in which a satisfactory solution has yet been achieved. The study also identifies methodological limitations and promising areas of future research, including geographic expansion, broader sector analysis, and exploring new technologies in tax administration.